HUBUNGAN KETAHANAN PANGAN DAN PENDAPATAN KELUARGA DENGAN KEJADIAN STUNTING PADA ANAK BALITA - Juwita, Ratna; Fentia, Lia; Yani, Sri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
One of the targets of the 2030 Sustainable Development Goals (SDGs) is to end all forms of malnutrition including achieving the 2025 international target to reduce stunting in children under five years old. Stunting not only impacts to health but also economic productivity, which is part of the Double Bourden Malnutrition (DBM) problem. The efforts that can be made include ending hunger and ensuring access to safe, nutritious, adequate food for all people, especially the poor and vulnerable, including babies and toddlers. This study aims to determine the relationship between food security and family income with the incidence of stunting in children under five years old. The study used an analytic method with a Case Control approach. The population in this study were mothers who had toddlers with a total sample size of 84 respondents consisting of 42 case groups and 42 control groups. The results showed that there was a significant relationship between food security (p.value 0.029) and family income (p.value 0.040) with the incidence of stunting in children under five years old. It is expected that families can improve food security and family income by utilizing the house yard by planting vegetables in pots, raising catfish using tarpaulins or used drums, and raising chickens. So that it can meet family needs without having to buy. So that it can meet nutritional needs and can prevent stunting in toddlersKeywords: Food Security; Family Income; Stunting.